Centrifugation | Analytical Ultracentrifugation - Peukert, Wolfgang; Walter, Johannes (Encyclopedia of Analytical Science, 2019)
Analytical ultracentrifugation is a highly accurate, reproducible and versatile technique to characterize the molecular weight, size, shape anisotropy, density and association of macromolecules and nanoparticles in solution. As a well-accepted analytical method, it has been applied widely in biology, biochemistry and polymer science to characterize (bio-)macromolecules and gains increasing interest in particle technology due to recent hard- and software developments. Multiwavelength detection providing access to spectral properties is one of the most important developments of the recent years. Experiments in the analytical ultracentrifuge are performed in sector shaped cells to measure the spatial and temporal concentration gradients using extinction, interference or fluorescence detectors. A moving boundary forms in sedimentation velocity experiments where high centrifugal forces are present. The rate of movement and shape of the boundary are determined by sedimentation and diffusion properties, respectively. The sedimentation depends on the analyte’s mass and frictional properties whereas diffusion is solely determined by frictional effects. Equilibrium studies are performed at lower rotor speeds where the mass transport due to sedimentation and diffusion balances, thus providing access to molecular weight distributions and interaction parameters. A variety of data analysis algorithms have been developed. Recently, multidimensional analysis has been established.
CRIS-Team Scopus Importer:2020-02-21
Keywords: Analytical ultracentrifugation; Association; Centrifugation; Density; Diffusion; Interactions; Lamm equation; Macromolecule; Mass; Multidimensional properties; Nanoparticle; Sedimentation; Shape; Size; Spectrum